Tumor Selective Ru(III) Schiff Bases Complexes, Discrimination of Ru(III)/Ru(II) Complexes in Solution: A DFT Study - Kahrović, Emira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
We recently reported a new Ru(III) complex (C1) with two Schiff bases and two chlorides that showed higher efficacy and improved cytotoxicity toward the triple-negative breast cancer cell line MDA-MB-231 compared to traditional antineoplastic drugs in use. In order to investigate hydrolysis as a possible activation step, DFT method of electronic structure calculation was used to obtain a preliminary insight for C1 under the conditions of the predicted atomic/ionic/molecular environment. The presence of both Na(+) and Mg(2+) counterions and reducing agents in every cell plasma give rise to several scenarios of C1 complexes interaction with living cell media. The DFT calculations showed the following: (i) the absolute energies of the complexes depend on the ruthenium oxidation state and the nature and type of association with the counter ion(s); (ii) the pairing of the C1-complex with the metal ion lowers the energy for solvated Mg(2+) compared to Na(+); (iii) the C1-Ru(II)/EtOH is more stable than the C1-Ru(III)/EtOH; and (iv) overall, the substitution of a chloride ligand by a water molecule is a thermodynamically unfavorable process. The proton from all Ru(III)Cl-OH2 species is more acidic compared to free water; consequently, under physiological conditions Ru(III)-ClOH2 does not exist. For Ru(II)-ClOH2 associated with Mg(2+), proton loss is a slightly favored process. Simulated substitution of Ru(III)-ClCl to Ru(III)-ClOH2 and the corresponding Ru(II) species suggest the following trend: from the a priori thermodynamic point of view hydrolysis of the C1 complex ranges from unfavorable to significantly prohibitive. Based on these calculations, hydrolysis does not appear to be a significant activation step of C1 as a potential drug.